The Oxford handbook of computational economics and finance - Chen, Shu-Heng, 1959-; Kaboudan, Mak; Du, Ye-Rong (New York : Oxford University Press, 2018)
This handbook provides a survey of both the foundations of and recent advances in the frontiers of analysis and action. It is both historically and interdisciplinarily rich and also tightly connected to the rise of digital society. It begins with the conventional view of computational economics, including recent algorithmic development in computing rational expectations, volatility, and general equilibrium. It then moves from traditional computing in economics and finance to recent developments in natural computing, including applications of nature-inspired intelligence, genetic programming, swarm intelligence, and fuzzy logic. Also examined are recent developments of network and agent-based computing in economics.
Computational Economics in the Era of Natural Computationalism: 50 Years after "The Theory of Self Reproducing Automata" / Shu-Heng Chen, Mak Kaboudan, Ye-Rong Du -- Economic and Financial Modeling with Genetic Programming - A Review / Clı́odhna Tuite, Michael O'Neill, Anthony Brabazon -- Algorithmic Trading Based on Biologically-inspired Algorithms / Vassilios Vassiliadis, Georgios Dounias -- Algorithmic Trading in Practice / Peter Gomber, Kai Zimmermann -- Computational Spatiotemporal Modeling of Southern California Home Prices / Mak Kaboudan -- Business Applications of Fuzzy Logic / Petr Dostál, Chia-Yang Lin -- Modeling of Desirable Socio-economic Networks / Akira Namatame, Takanori Komatsu -- Computational Models of Financial Networks, Risk and Regulatory Policies / Kimmo Soramäki -- From Minority Games to $-Games / Jorgen Vitting Andersen -- An Overview and Evaluation of The CAT Market Design Competition / Tim Miller, Jinzhong Niu, Martin Chapman, Peter McBurney -- Agent-Based Macroeconomic Modeling and Policy Analysis: The Eurace@Unibi Model / Herbert Dawid, Simon Gemkow, Philipp Harting, Sander van der Hoog, Michael Neugart -- Dynamic Stochastic General Equilibrium Models: A Computational Perspective / Michel Juillard -- Agent-Based Models for Economic Policy Design / Michael Neugart, Matteo Richiardi -- Computational Economic Modeling of Migration / Anna Klabunde -- Computational Industrial Economics / Myong-Hun Chang -- Agent-Based Modelling for Financial Markets / Giulia Iori, James Porter -- Agent-Based Models of the Labor Market / Frank Westerhoff, Reiner Franke -- The Emerging Standard Neurobiological Model of Decision Making / Shih-Wei Wu, Paul W. Glimcher -- The Epistemology of Simulation, Computation and Dynamics in Economics / K. Vela Velupillai -- Tax-rate Rules for Reducing Government Debt: An Application of Computational Methods for Macroeconomic Stabilization
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 30, 2018).
Keywords: Economics -- Data processing; Economics, Mathematical; Finance -- Data processing